Effective community engagement in one health research in Sub-Saharan Africa: a systematic review - Sidney Sangong; Farrukh Ishaque Saah; Luchuo Engelbert Bain (One Health Outlook)
Abstract Background The one health (OH) approach, linking human, animal, and environmental health, relies on effective community engagement (CE), education, stewardship, and effective regional and global partnerships. For real impact, communities should be at the centre of research agenda setting and program implementation. This review aimed at synthesizing empirical evidence on how communities are involved in one health research. Specifically, the review aimed at documenting the extent of community involvement in one health research, as well as to identify the barriers and facilitators to effective community engagement in one health research in sub Saharan Africa. Methods The study was a systematic review conducted using the 2020 Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Empirical peer-reviewed research articles on community engagement in one health research published from January 2000 to September 2023 in English or French were retrieved from seven databases: MEDLINE, EMBASE, CINAHL, Cochrane Library, WHO Afro Library, the National Institute for Health Research, and African Journals Online databases. The extracted data from the included studies were analysed using a thematic synthesis approach. Results The final review and synthesis included eight studies. The extent of CE in the one health research approach is quite limited. Two main best practices of CE in OH research were: 1) Awareness raising on OH research through social mobilization, rural outreach sensitization, and wide community assembly and 2) Building local capacity through community-based OH Training and Leadership workshops. The barriers to effective CE included: inadequate community research literacy levels, contextual disparities in CE, inadequate dissemination of research findings, language barriers and ineffective and uncoordinated stakeholder involvement. Conclusion The review underscores the importance of effective CE in one health research. The best practices for CE in one health research are raising awareness and co-creation which should guide future initiatives. There are cultural, geographical, linguistic, and educational constraints that pose barriers to CE, requiring a more integrated and community-centric approach to one health research in SSA. An effective CE in one health research through this approach will ultimately lead to more effective responses and control of zoonotic disease outbreaks.